Factors Causing the High Number of Divorce Cases in the Tegal City Religious Court - A Komarudin; Sayid Malik Hasan; Ikhsan Bakhtiar; Almiatun Anikoh; Fadli Muhammad Subhan; Nur Attiqa Syifa’ul Amri; Louise Anatasya Ramadhani; Fatkhul Rizqi Ramadhan; M Zidni Ilman; Ahmad Farisul Haq; M. Fajar Zuhri (al-Afkar, Journal For Islamic Studies, 2025)
The cause of divorce is a condition where the husband or wife uses it as an excuse to end or sever the marriage bond. There are cases where the wife files a divorce suit at the Tegal Religious Court, when one party can harm the other party, it always has a bad impact on the other party. The husband is not a good priest. in the household, never asking for congregational prayers during marriage, not guiding the wife and children in worship then this is what is said to be a moral crisis which can have a bad impact when the marriage continues and can threaten religion, life, nashab and property. This makes us interested in discussing this issue further. Dissolution of marriage is a legal term used in marriage law to explain divorce or the end of a marriage relationship between a man and a woman who have been living as husband and wife. The forms of divorce in Indonesia in Marriage Law Number 1 of 1974 appear to be divided simply, namely due to death, divorce, and by court decision.Divorce is a lawsuit filed by a wife against her husband to the Religious Court for certain reasons. Divorce on the basis of contested divorce occurs because there is a court decision. The divorce procedure is regulated in Government Regulation No. 9 of 1975 articles 20 to article 36 jo. Article 73 to Article 83 of Law No.7 of 1989.